Persistence of High Income Inequality and Banking Crises: 1980-2010 - Giorgio Bellettini; Flavio Delbono (Center for Economic Studies and ifo Institute (CESifo), 2013)
Differently from Atkinson and Morelli (2011) who detect no clear link between increases in income inequality and systemic banking crises, we show that a large majority of crises occurred between 1982 and 2008 have been preceded by persistently high levels of income inequality. Such association is robust when considering Gini values for incomes after-tax as well as before-tax and transfers. Moreover, we investigate the pattern of income inequality levels before and after a group of banking crises and the relative levels of income inequality in a large sample of OECD countries that did not experience banking crises between 1980 and 2010.
Keywords: E00; 330